Family Structure and Secondary Exposure to Violence in the Context of Varying Neighborhood Risks and Resources. (March 2021) - Stritzel, Haley; Smith Gonzalez, Chelsea; Cavanagh, Shannon E.; Crosnoe, Robert
Secondary exposure to violence in the community is a prevalent developmental risk with implications for youths' short- and long-term socioemotional functioning. This study used longitudinal, multilevel data from the Project on Human Development in Chicago Neighborhoods to consider how family structure, including parental instability, is associated with youths' secondary exposure to violence across diverse neighborhood contexts. Results showed that both living in a stable single-parent household and experiencing parental instability were associated with greater secondary exposure to violence compared with living in a stable two-parent household. The associations between having a single parent or experiencing parental instability and secondary exposure to violence were especially strong in neighborhoods with high levels of crime and strong neighborhood ties.